Acceptance of a vaccine against COVID-19 - a systematic review of surveys conducted worldwide - Sněhota, Martin; Vlčková, Jana; Čížková, Kateřina; Vachutka, Jaromír; Kolářová, Hana; Klásková, Eva; Kollárová, Helena (Bratislavské lekárske listy, 2021)
OBJECTIVES: The most promising strategy for managing COVID-19 pandemic is achieving sufficient vaccination rate worldwide. The question is how many people will be willing to get vaccinated. STUDY DESIGN: We systematically reviewed peer-reviewed manuscripts monitoring people ́s intention to receive a vaccine against COVID-19. METHODS: Up to December 28, 2020 we identified 62 relevant peer-reviewed articles in PubMed, Web of Science, Scopus and GoogleScholar. RESULTS: Total sample size was 118 855 respondents with overall average COVID-19 vaccine acceptance rate of 72.5% which is “just” the level estimated to be sufficient for reaching herd immunity threshold. Surprisingly, healthcare workers showed smaller interest in receiving the vaccine when compared to general adult population and university students. On the other hand, their attitude to vaccination did not change over time. In case of general adult population, the longer the pandemic lasts, the smaller proportion of population wants to get vaccinated. Vaccination intentions were independent of gross domestic product and human development index. CONCLUSION: Willingness of population to receive COVID-19 is just at the herd immunity threshold and it is decreasing over time (Tab. 2, Fig. 3, Ref. 110).
Keywords: Vaccination; Clinical Studies as Topic; adherence a compliance při léčbě; vakcinace; COVID-19 Vaccines; klinická studie jako téma; Treatment Adherence and Compliance; vakcíny proti COVID-19; lidé; Humans; Attitude; postoj